Inflammatory and immune responses in the cochlea: potential therapeutic targets for sensorineural hearing loss - Fujioka, Masato; Okano, Hideyuki; Ogawa, Kaoru (Frontiers in Pharmacology, 2014)
The inner ear was previously assumed to be an “immune-privileged” organ due to the existence of its tight junction-based blood-labyrinth barrier. However, studies performed during the past decade revealed that the mesenchymal region of the cochlea, including its lateral wall, is a common site of inflammation. Neutrophils do not enter this region, which is consistent with the old dogma; however, bone marrow-derived resident macrophages are always present in the spiral ligament of the lateral wall and are activated in response to various types of insults, including noise exposure, ischemia, mitochondrial damage and surgical stress. Recent studies have also revealed another type of immune cell, called perivascular melanocyte-like macrophages (PVM/Ms), in the stria vascularis. These dedicated antigen-presenting cells also control vascular contraction and permeability. This review discusses a series of reports regarding inflammatory/immune cells in the cochlear lateral wall, the pathways involved in cochlear damage and their potential as therapeutic targets.